2021
DOI: 10.5194/acp-21-6811-2021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recent lower-stratospheric ozone trends in chemistry climate models

Abstract: Abstract. Recent observations show a significant decrease in lower-stratospheric (LS) ozone concentrations in tropical and mid-latitude regions since 1998. By analysing 31 chemistry climate model (CCM) simulations performed for the Chemistry Climate Model Initiative (CCMI; Morgenstern et al., 2017), we find a large spread in the 1998–2018 trend patterns between different CCMs and between different realizations performed with the same CCM. The latter in particular indicates that natural variability strongly inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 82 publications
4
39
0
Order By: Relevance
“…Recently, the ozone simulated by 31 CCMs participating in the Chemistry-Climate Model Initiative Phase-1 (CCMI-1) has been analyzed, and it was shown that the pattern of the signal in LSO varies greatly even between different realizations of the experiment performed with the same CCM (Dietmüller et al, 2021). The question is why models cannot reproduce the persistent and statistically robust declining trends in near-global LSO.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the ozone simulated by 31 CCMs participating in the Chemistry-Climate Model Initiative Phase-1 (CCMI-1) has been analyzed, and it was shown that the pattern of the signal in LSO varies greatly even between different realizations of the experiment performed with the same CCM (Dietmüller et al, 2021). The question is why models cannot reproduce the persistent and statistically robust declining trends in near-global LSO.…”
mentioning
confidence: 99%
“…These results suggest that to study long-term ozone trends in dynamically controlled regions, it is desirable to analyze different ensemble members of the experiment separately because ensemble-averaging suppresses the variability. In contrast, Dietmüller et al (2021) suspect that the models have difficulties reproducing the observed LSO trend because of extreme natural variability at the beginning or end of the observed period , or because natural variability in QBO and BDC is not adequately simulated. Thus, small inadequacies in atmospheric dynamics might be the reason why models do not demonstrate robust LSO negative tendencies, amplified by the strong internal ozone variability (Shangguan et al, 2019).…”
mentioning
confidence: 99%
“…Our results also prove the potential of GWs to alter the ozone variability and its trends via mixing in the surf zone or advection from lower latitudes. The evidence for a link between polar vortex dynamics and the parameterized OGWD via PWs stipulates further research of the uncertainty in polar vortex projections (Manzini et al, 2014;Ayarzagüena et al, 2020) or ozone variability (Dietmüller et al, 2021). Given all the assumptions and tuning employed in the OGW parameterization scheme, this indication of surprisingly wide ranging effects of parameterized OGWD in the model prompts validation in GW resolving datasets and makes an additional case for improving of the parameterizations in CCMs.…”
Section: Discussionmentioning
confidence: 78%
“…In future work a standalone metric could be developed with even lower false alarm rate. Dietmüller et al (2021) discussed in detail the model spread in ozone variability and trends in the lower stratospheric mid latitudes, however, they could not identify a clear cause for this spread. Our results now show that also the representation of GWs have the potential to alter ozone variability and trends in the lower stratospheric mid latitudes in chemistry climate models and hence can play a role for the inter-model spread.…”
Section: Contextualizationmentioning
confidence: 94%
“…At the same time, in the lower stratosphere, atmospheric composition and ozone levels are driven by the climate-impacted changes in the Brewer-Dobson circulation and by seasonal-to-decadal variability in stratospheretroposphere exchange. These processes are difficult to discern and predict based solely on ozone or other atmospheric composition observations (Ball et al, 2019(Ball et al, , 2020Abalos et al, 2019;Orbe et al, 2017;Strahan et al, 2020;Dietmüller et al, 2021). Analyses of the processes that are responsible for ozone changes through atmospheric chemistry and dy-namical transport rely on the development of climate chemistry models (CCMs, Morgenstein et al, 2017).…”
mentioning
confidence: 99%